2021
DOI: 10.3389/fpsyg.2021.702819
|View full text |Cite
|
Sign up to set email alerts
|

Webcams, Songs, and Vocabulary Learning: A Comparison of In-Person and Remote Data Collection as a Way of Moving Forward With Child-Language Research

Abstract: This article evaluates a testing procedure for collecting eye-gaze data with toddlers and preschoolers during a word-learning task. We provide feasibility and precision data by comparing performance in an in-person version of the study (conducted under controlled conditions in the lab), with performance in a virtual version in which participants completed the testing procedure from home. Our data support the feasibility of collecting remote eye-gaze data with young children, and present it as a viable alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…Over the past few years, developmental scientists have published on the best practices for online data collection methods (Frank et al, 2016;Garrisi et al, 2020;Lourenco and Tasimi, 2020;Manning et al, 2020;Nussenbaum et al, 2020;Rhodes et al, 2020;Sheskin et al, 2020;Morini and Blair, 2021;Su and Ceci, 2021). These studies agree that while online data collection methods are still in their infancy, online measurements have become a promising platform for developmental psychology research.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Over the past few years, developmental scientists have published on the best practices for online data collection methods (Frank et al, 2016;Garrisi et al, 2020;Lourenco and Tasimi, 2020;Manning et al, 2020;Nussenbaum et al, 2020;Rhodes et al, 2020;Sheskin et al, 2020;Morini and Blair, 2021;Su and Ceci, 2021). These studies agree that while online data collection methods are still in their infancy, online measurements have become a promising platform for developmental psychology research.…”
Section: Introductionmentioning
confidence: 93%
“…However, only a few studies provide empirical evidence comparing online methods to face-to-face methods. For example, Morini and Blair (2021) examined the feasibility of collecting remote eye-gaze data with children. They compared their online sample to a previously collected face-to-face sample, during which they found their online data collection methods to be reliable and sufficient in conducting developmental language research (Morini and Blair, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Testing this more challenging word learning task may help us better understand the extent to which different e-reading modalities impact language development in young children, and the role that different levels of engagement might play in learning from shared reading. As highlighted by Morini and Blair (2021), there are many factors to consider when collecting data remotely, including the duration of the session and the amount of distractions around the child.…”
Section: The Acceleration Of Smsr As a Results Of The Pandemicmentioning
confidence: 99%
“…Emerging research from Shields et al (2021) has shown that virtual interactions via video-chat are effective for children's learning. There are some concerns regarding research conducted via video-chat as such settings tend to be more varied and distracting for children and produce challenges to observations and data collection (Chuey et al, 2021;Morini and Blair, 2021). However, Chuey et al (2021) found that participant sessions that are moderated by a live experimenter maintain the interactive experience of in-person studies.…”
Section: The Acceleration Of Smsr As a Results Of The Pandemicmentioning
confidence: 99%
“…Whereas web-based data collection in adults is extensively and successfully used and several well-established RT effects have been replicated in web-based research ( Crump et al, 2013 ; Simcox and Fiez, 2014 ), there are only a few recent web-based studies with children and infants ( Scott et al, 2017 ; Nussenbaum et al, 2020 ; Rhodes et al, 2020 ; Bambha and Casasola, 2021 ; Vales et al, 2021 ). Recent studies collecting RTs with adults and children have shown little to no difference between laboratory-based and web-based samples ( de Leeuw and Motz, 2016 ; Hilbig, 2016 ; Bridges et al, 2020 ; Nussenbaum et al, 2020 ; Morini and Blair, 2021 ; Silver et al, 2021 ; Vales et al, 2021 ) as well as no big differences between browsers (e.g., Chrome and Internet Explorer) or experiment builders (e.g., Pavlovia and Gorilla) ( Kochari, 2019 ; Anwyl-Irvine et al, 2020 ; Sauter et al, 2020 ). In addition, it is difficult to clearly state whether potential differences may be any greater than the difference between two laboratory-based collected samples ( Nussenbaum et al, 2020 ).…”
Section: Natural Stimulimentioning
confidence: 99%